Filtration and Antibacterial Properties of Bacterial Cellulose Membranes for Textile Wastewater Treatment - Zelal Isık; Ali Unyayar; Nadir Dizge (Hamadan University of Medical Sciences, 2018)
Bacterial cellulose (BC) which is characterized by numerous original properties including high purity, crystallinity and mechanical strength has the same molecular formula as cellulose from plant source. The aim of this study was to investigate the possibilities of using environmentally friendly BC membranes for membrane separation. BC membranes produced by Acetobacter xylinum were grown in a kombucha tea medium. The effect of cultivation time on filtration properties of BC membranes was tested (from 10 to 30 days). Dead-end filtration was used to determine pure water and permeate fluxes. The hydraulic permeability coefficients (Lp ) of BC membranes were 20.5, 16.1, 4.5 L/m2 h bar for 10, 20, 30 days, respectively. The effects of applied pressure (2.5, 7.5, 12.5 bar) and solution pH (5.0, 7.0, 8.8) were examined on color and chemical oxygen demand (COD) removal. The highest color and COD removals were 85.9 and 73.8% for BC-10 and 90.9 and 75.1% for BC-20 membranes at 12.5 bar pressure and pH 5.0. Moreover, silver nanoparticles with different concentrations (2, 4, and 8 mM) were grown on BC-20 membrane to investigate antibacterial properties of the composite membrane. The results showed that BC membrane could be used to develop eco-friendly antibacterial membranes with potential applications in color and COD removal from textile wastewater.